2022
DOI: 10.1038/s41392-022-01127-3
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco carcinogen induces tryptophan metabolism and immune suppression via induction of indoleamine 2,3-dioxygenase 1

Abstract: Indoleamine 2,3-dioxygenase 1 (IDO1), the enzyme that catabolizes tryptophan (Trp) metabolism to promote regulatory T cells (Tregs) and suppress CD8+ T cells, is regulated by several intrinsic signaling pathways. Here, we found that tobacco smoke, a major public health concern that kills 8 million people each year worldwide, induced IDO1 in normal and malignant lung epithelial cells in vitro and in vivo. The carcinogen nicotine-derived nitrosaminoketone (NNK) was the tobacco compound that upregulated IDO1 via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Notably, the combination of 1‐MT and BAY876 (combo) exhibited the most potent tumor growth inhibition among the four groups (Figures 6C–E). In addition, 1‐MT significantly suppressed IDO1 activity (reflected by the ratio of Kyn/Trp 44 ) in serum (Figure 6H). Further, terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining of tumor tissue sections showed that 1‐MT had a proapoptotic effect while the combo led to a more robust proapoptotic effect than the monotherapy (Figure 6I).…”
Section: Resultsmentioning
confidence: 92%
“…Notably, the combination of 1‐MT and BAY876 (combo) exhibited the most potent tumor growth inhibition among the four groups (Figures 6C–E). In addition, 1‐MT significantly suppressed IDO1 activity (reflected by the ratio of Kyn/Trp 44 ) in serum (Figure 6H). Further, terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining of tumor tissue sections showed that 1‐MT had a proapoptotic effect while the combo led to a more robust proapoptotic effect than the monotherapy (Figure 6I).…”
Section: Resultsmentioning
confidence: 92%
“…Our previous study demonstrated that KP is crucial for the etiopathogenesis of periodontal diseases 14 . In the literature, it was shown that smoking has impacts on KP 18,19,39 . Based on this information, in this study, the influence of smoking and periodontal inflammation on salivary and serum TRP‐KYN metabolism was investigated and it was revealed that the KYN/TRP ratio was significantly decreased in saliva in association with periodontitis.…”
Section: Discussionmentioning
confidence: 87%
“…14 In the literature, it was shown that smoking has impacts on KP. 18,19,39 Based on this information, in this study, the influence of smoking and periodontal inflammation on salivary and serum TRP-KYN metabolism was investigated and it was revealed that the KYN/TRP ratio was significantly decreased in saliva in association with periodontitis. Strikingly, while the salivary KYN/TRP ratio was lowest in the NS-P group, the serum KYN/TRP ratio was the lowest in the S-P group.…”
Section: Discussionmentioning
confidence: 99%
“… 83 However, within the tumor niche, cancer cells, MDSCs, TAMs, suppressive DCs, and cancer-associated fibroblasts, among other cell types, exhibit upregulated expression of indoleamine 2,3-dioxygenase (IDO), which metabolizes tryptophan into suppressive kynurenine to promote Tregs and suppress CD8 + T cell function. 84 86 Most cancer cells overexpress IDO, and the level of kynurenine in the microenvironment is associated with poor prognosis in multiple solid and hematological malignancies. 87 Kynurenine has been found to bind to the aryl hydrocarbon receptor (AHR) in naïve CD4 + T cells, which promotes Treg differentiation.…”
Section: Metabolic Characteristics and Nutrient Availability In The T...mentioning
confidence: 99%